TGF-β1 expression by glioma C6 cells in vitro - Liubich, L.D.; Kovalevska, L.M.; Lisyany, M.I.; Semenova, V.M.; Malysheva, T.A.; Stayno, L.P.; Vaslovych, V.V. (Experimental Oncology, 2017)
The aim of the work was to study the impact of fetal rat brain cell supernatant (FRBCS) on the expression of transforming growth factor β1 (TGF-β1) and p53 in C6 cells of rat glioma in vitro. Materials and Methods: FRBCS was obtained from suspensions of fetal rat brain cells on the 14th (E14) day of gestation. C6 glioma cells were cultured for 48 h in the presence of FRBCS or FRBCS + anti-TGF-β1 monoclonal antibody. Immunocytochemical staining for TGF-β1 and p53 was performed. Results: The proportion of TGF-β1-immunopositive tumor cells in C6 glioma cultures was statistically significantly higher than in the control cell cultures of normal fetal rat brain. FRBCS reduced the proportion of TGF-β1-immunopositive tumor cells and increased the proportion of p53-immunopositive cells in C6 glioma cultures. In cells cultured with FRBCS + anti-TGF-β1 monoclonal antibody, the above effects of FRBCS were abrogated. Conclusion: The obtained results suggest that TGF-β1 seems to be responsible for decrease in TGF-β1 expression and increase in p53 expression in C6 glioma cells treated with FRBCS.